Evolution of a sand-rich submarine channel–lobe system, and the impact of mass-transport and transitional-flow deposits on reservoir heterogeneity: Magnus Field, Northern North Sea. Issue 3 (2021) - Steventon, Michael J.; Jackson, Christopher A.-L.; Johnson, Howard D.; Hodgson, David M.; Kelly, Sean; Omma, Jenny; Gopon, Christine; Stevenson, Christopher; Fitch, Peter
No abstract available